EKSPLORASI KEMAMPUAN KOGNITIF SISWA TERHADAP KEMAMPUAN MEMPREDIKSI, MENGOBSERVASI DAN MENJELASKAN DITINJAU DARI GENDER - Friska Octavia Rosa (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The study aims to explore the students' cognitive abilities of predicting, observing and explaining skills in terms of student's gender. In this study used students as many as 24 students with 16 female students and 8 male students. The research instrument used is a matter of test and observation sheet. Based on the data obtained in the study concluded that the cognitive abilities of students on average are in the high category and dominated by female students. The results of analysis indicate that there are differences, the ability of female students is better than male students.